2022
DOI: 10.3390/nu14153032
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Glycation End Products Are Associated with Diabetes Status and Physical Functions in Patients with Cardiovascular Disease

Abstract: Advanced glycated end products (AGEs) accumulate systemically and cause diabetes complications. However, whether noninvasive measurable AGEs are associated with diabetes status and physical functions remains unclear. One hundred and ten patients with cardiovascular disease (CVD) who underwent outpatient cardiac rehabilitation were included. AGEs scores, using AGEs sensors, were evaluated concomitantly with a physical evaluation, including testing the isometric knee extension strength (IKES) and 6 min walking d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The relationship between BMR, body composition, and physical activity is well established [ 38 ]. Thus, the negative correlation between sAF and BMR may indirectly reflect the beneficial effect of higher physical activity on glycation severity and sAF values, i.e., lowering them [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between BMR, body composition, and physical activity is well established [ 38 ]. Thus, the negative correlation between sAF and BMR may indirectly reflect the beneficial effect of higher physical activity on glycation severity and sAF values, i.e., lowering them [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that AGEs may cause cardiac and vascular dysfunction in two ways: vascular stiffness and cardiac fibrosis through the cross-linking of elastin and collagen; inflammation and oxidative stress through AGER. 22 Both in vivo and in vitro studies conducted by Zhong et al suggest that the endoplasmic reticulum stress induced by AGEs can mediate the activation of PERK/CaN/NFAT4c signal transduction in cardiac microvascular endothelial cells, and then trigger the transcription of targeted genes, leading to apoptosis, inflammation, and micro thrombosis, thereby exacerbating microvascular dysfunction in non-obstructive coronary artery disease. 23 Liang B et al also found that the AGEs-RAGE axis mediates myocardial fibrosis by activating autophagy-induced cardiac fibroblasts in heart failure.…”
Section: Discussionmentioning
confidence: 99%